Pengaruh Stres Kerja, Kedisiplinan dan Reward Terhadap Kinerja Pegawai (PERUMDAM Mojopahit Mojokerto) - Kholifah, Diajeng; Firdaus, Vera (Indonesian Journal Publisher, 2024)
This study aims to determine the effect of work stress, discipline and reward on the performance of Perumdam employees (Drinking Water Regional Public Companies) Mojopahit Mojokerto. This research is a quantitative research. Data sources in this study were obtained through interviews and the distribution of questionnaires of 100 employees using proportional stratified random sampling techniques. The analysis technique used in this study was path analysis. The results of research obtained based on the validity test showed that all statements in the questionnaire were declared valid. For the reliability test of all variables there is only one obtained a composite reable value or the Cronbach Alpha value is declared reliable. And hypothesis testing based on the value of T-statistics and p values ​​that work stress affects employee performance. Discipline affects employee performance. Rewards affect employee performance.